2011
DOI: 10.1109/tpami.2010.73
|View full text |Cite
|
Sign up to set email alerts
|

Global Ridge Orientation Modeling for Partial Fingerprint Identification

Abstract: Abstract-Identifying incomplete or partial fingerprints from a large fingerprint database remains a difficult challenge today. Existing studies on partial fingerprints focus on one-to-one matching using local ridge details. In this paper, we investigate the problem of retrieving candidate lists for matching partial fingerprints by exploiting global topological features. Specifically, we propose an analytical approach for reconstructing the global topology representation from a partial fingerprint. Firstly, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 20 publications
0
63
0
Order By: Relevance
“…These include singular points and pattern type [3], ridge flow map (or orientation field) , ridge wavelength map (or frequency map) [4,5], skeleton , and crease [6]. However, these studies primarily address full fingerprint matching and, to our knowledge, there is no published algorithm on using extended features for latent matching.…”
Section: IImentioning
confidence: 99%
“…These include singular points and pattern type [3], ridge flow map (or orientation field) , ridge wavelength map (or frequency map) [4,5], skeleton , and crease [6]. However, these studies primarily address full fingerprint matching and, to our knowledge, there is no published algorithm on using extended features for latent matching.…”
Section: IImentioning
confidence: 99%
“…The image area without operative ridges and furrows is first discarded since it only holds background information. Then bound of remaining effective area is sketched out since the minutia in bound region are confusing with those spurious minutia that are generated when the ridges are out of the sensor [9].…”
Section: Thinning Of Imagementioning
confidence: 99%
“…Thus, they had concluded that the proposed ridge feature gave additional information for fingerprint matching with little increment in template size and used in conjunction with existing minutiae features to increase the accuracy and robustness of fingerprint recognition systems. Some [9] presented an investigation of the problem of retrieving candidate lists for matching partial fingerprints by exploiting global topological features. They proposed an analytical approach for reconstructing the global topology representation from a partial fingerprint.…”
Section: Related Workmentioning
confidence: 99%